Triple Negative Breast Carcinoma: A Comparative Study between Breast Lesion and Lymph Node Metastases: A Preliminary Study. (30th June 2011) - Parada, David; Peña, Karla; Riu, Francesc; Hernandez, Pilar
Abstract : Aims and Background . Triple negative breast carcinoma is a genetic and molecular subtype of breast carcinoma with poor prognosis. Some immunohistochemistry studies have been proposed to identify BLBC. Most studies consider primary breast carcinoma but not metastases. Methods . Immunohistochemical characteristics in 11 triple negative breast carcinomas were studied in both primary lesions and lymph node metastases. All cases were reevaluated to estrogen and progesterone receptors and HER2-Neu. An FISH probe for HER2/neu was also performed. Immunohistochemical studies were performed with cytokeratin 5/6, 17, Cam 5.2, p63, EGFR, and Ki-67 in breast carcinoma and lymph node metastases. Results . The age of the patients ranged between 42 and 73 years (mean 53), and the mean followup was 68.25 months. A total of 54.55% of the patients were disease-free, and 45.45% died of carcinoma. Axillary lymph nodes maintained triple negative phenotype (11/11). Metastatic tumors showed CAM 5.2 (81.83%) and EGFR (72.73%) expression. Basal marker expression was variable in primary carcinoma and lymph node metastases (63.64%). Conclusions . Triple negative breast carcinomas maintained this immunoprofile at lymph node metastases. Triple negative carcinomas showed variable expression of basal cell markers.